Qualitative and quantitative HIV antibodies and viral reservoir size characterization in vertically infected children with virological suppression. (30th December 2016) - Brice, Josephine; Sylla, Mariam; Sayon, Sophie; Telly, Fatoumata; Bocar-Fofana, Djeneba; Murphy, Robert; Lambert-Niclot, Sidonie; Todesco, Eve; Grude, Maxime; Barin, Francis; Diallo, Souleymane; Pillay, Deenan; et al.
Abstract : Background: Absence of detectable viraemia after treatment cessation in some vertically HIV-infected (VHIV) children suggests that early initiation of HAART could lead to functional cure. Objectives: We described the factors associated with HIV antibody levels and the viral reservoir size in HAART-treated VHIV children. Methods: Study included 97 VHIV children with virological suppression, in Bamako, Mali. The anti-gp41 antibody activities and HIV serostatus were assessed. The viral reservoir size was measured by quantifying total cell-associated HIV DNA. Results: Among the children studied, the median total HIV DNA level was 445 copies/10 6 cells (IQR = 187–914) and the median anti-gp41 antibody activity was 0.29 OD (IQR = 0.18–0.75). Low activity of anti-gp41 antibodies was associated with a younger age of HAART initiation ( P = 0.01). Overall, eight HIV-1 seroreversions were identified. Conclusions: Study identified potential candidates with low viral reservoir and low antibody levels or activities for future trials aiming to reduce HIV-1 reservoir to limit HAART duration.